2023
DOI: 10.3390/microorganisms11010112
|View full text |Cite
|
Sign up to set email alerts
|

Oral Prevalence of Akkermansia muciniphila Differs among Pediatric and Adult Orthodontic and Non-Orthodontic Patients

Abstract: Akkermansia muciniphila (AM) is one of many highly abundant intestinal microbes that influences homeostasis and metabolic disorders and may also play a role in oral disorders. However, there is little evidence regarding the oral prevalence of this organism. Based upon this lack of evidence, the primary goal of this project is to survey an existing saliva repository to determine the overall prevalence of this organism and any associations with demographic or patient characteristics (age, sex, body mass index, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…To facilitate the molecular screening, saliva samples were first thawed and processed to isolate the DNA using the TRIzol reagent from Invitrogen (Waltham, MA, USA), as previously described in [ 26 , 27 ]. In brief, samples were thawed at room temperature and then vortexed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate the molecular screening, saliva samples were first thawed and processed to isolate the DNA using the TRIzol reagent from Invitrogen (Waltham, MA, USA), as previously described in [ 26 , 27 ]. In brief, samples were thawed at room temperature and then vortexed.…”
Section: Methodsmentioning
confidence: 99%
“…To this mixture, 200 µL of molecular biology grade Chloroform from Fisher Scientific (Waltham, MA, USA) was added and incubated on ice for ten minutes prior to centrifugation at 12,000× g relative centrifugal force (RCF) at 4 °C in a refrigerated microcentrifuge from Eppendorf—Model 5425 (Hamburg, Germany). Following centrifugation and separation, the upper aqueous phase (approximately 300 to 400 µL) was transferred to a new sterile microcentrifuge tube and an equal volume of molecular biology grade Isopropanol from Fisher Scientific (Waltham, MA, USA) was added to precipitate the DNA from each sample [ 26 , 27 ]. All samples were then centrifuged again for ten minutes at 12,000× g RCF at 4 °C in a refrigerated microcentrifuge from Eppendorf—Model 5425 (Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies from this group have analyzed the changes in oral microbial prevalence and changes to specific microbial populations, including Scardovia wiggsiae, Selenomonas noxia, Streptococcus mutans, and Porphyomonas gingivalis, which may be elevated among orthodontic patient populations in particular [23][24][25]. In addition, another study from this group recently found that the commensal bacterium Akkermansia muciniphila (which also exhibits anti-inflammatory properties) is decreased among adults versus pediatric patients, as well as among orthodontic versus non-orthodontic patients regardless of age within this clinic population [26]. In contrast, the results from the current study appear to suggest that the oral prevalence of Slackia exigua may be higher among orthodontic patients than non-orthodontic patients, which holds true regardless of age.…”
Section: Discussionmentioning
confidence: 89%
“…Exigua, derived from Latin, means sparse, reflecting the difficult and feeble growth of this organism on microbiological media (2,3). Originally known as Eubacterium exiguum, it was later reclassified by Wade et al as Slackia exigua in 1999 (4). Wade and co-workers reported a 94.5% similarity in the 16S rRNA gene sequence between Eubacterium exiguum found in human oral lesions and Peptostreptococcus heliotrinreducens (reclassified as Slackia heliotrinireducens) isolated from the sheep rumen.…”
Section: Introductionmentioning
confidence: 99%